GE_GERICHTE C/9733/2010 vom 12. Januar 2018 - GE Cour de justice (2018)
PROTECTION DE L'ENFANT ; CURATELLE ÉDUCATIVE ; FRAIS JUDICIAIRES ; ASSISTANCE JUDICIAIRE | CC.308.al1; LaCC.81.al1; CPC.118.alB; RTFMC.54